1987
DOI: 10.1093/geronj/42.5.466
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Antimicrobial Proteins from the Parotid Glands of Different Aged Healthy Persons

Abstract: The secretion of three antimicrobial proteins from the parotid glands of 82 generally healthy men and women, 22 to 81 years in age, was examined. No change was observed in the levels of secretory IgA, but statistically significant, modest elevations (approximately 50 to 100%) of lactoferrin, in both unstimulated and stimulated secretions, and lysozyme, in unstimulated secretions, were detected when results were expressed as mg antimicrobial protein/100 ml saliva. However, these alterations were not observed if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 0 publications
2
18
1
Order By: Relevance
“…Parotid and whole saliva from healthy non-medicated subjects showed no age changes in flow rate or concentrations of antimicrobial and proline-rich proteins. This was the case in both cross-sectional and longitudinal studies (Aguirre et al, 1987;Fox et al, 1987;Wu et al, 1993;Narhi et al, 1994). One paper has reported higher levels of parotid slgA in aged subjects (Arranz et al, 1992), but this has not been confirmed by others (Ganguly et al, 1986;Aguirre et al, 1987;Fox et al, 1987).…”
Section: (D) Long-term Changementioning
confidence: 89%
See 1 more Smart Citation
“…Parotid and whole saliva from healthy non-medicated subjects showed no age changes in flow rate or concentrations of antimicrobial and proline-rich proteins. This was the case in both cross-sectional and longitudinal studies (Aguirre et al, 1987;Fox et al, 1987;Wu et al, 1993;Narhi et al, 1994). One paper has reported higher levels of parotid slgA in aged subjects (Arranz et al, 1992), but this has not been confirmed by others (Ganguly et al, 1986;Aguirre et al, 1987;Fox et al, 1987).…”
Section: (D) Long-term Changementioning
confidence: 89%
“…This was the case in both cross-sectional and longitudinal studies (Aguirre et al, 1987;Fox et al, 1987;Wu et al, 1993;Narhi et al, 1994). One paper has reported higher levels of parotid slgA in aged subjects (Arranz et al, 1992), but this has not been confirmed by others (Ganguly et al, 1986;Aguirre et al, 1987;Fox et al, 1987). Submandibular/sublingual saliva has not been extensively studied, but lower levels of MG1 and MG2 have been reported in healthy non-medicated older adults (Denny et al, 1991;Navazesh et al, 1992).…”
Section: (D) Long-term Changementioning
confidence: 95%
“…In normal healthy individuals, histatin levels decrease with age (Johnson et al 2000). In contrast, the concentrations of other salivary proteins show little change during aging in healthy, unmedicated people (Fox et al 1987;Wu et al 1993). Histatin levels are increased in otherwise healthy individuals who have experienced recurrent oral Candida infections (Bercier et al 1999) and in HIV-positive patients (Atkinson et al 1990).…”
mentioning
confidence: 99%
“…Studies conducted among hospitalized [4] and nonhospitalized [5][6][7] geriatric populations have demonstrated altered production of the salivary antimicrobial proteins lysozyme and lactoferrin compared to younger healthy adult populations. Lysozyme, a 14-kD ubiquitous protein also known as muramidase, exhibits potent bactericidal and fungicidal properties against pathogenic microorganisms such as oral streptococci [8] and Candida albicans [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Younger patients with immunodeficiencies such as HIV infection [11][12][13] and serum immunoglobulin A deficiency [14] also exhibit impaired production of these key defense factors compared to their immunocompetent counterparts. These studies suggest that diminished production of antimicrobial factors may contribute to the increased risk of oral mucosal disease among the elderly [4][5][6][7] and persons with severe immunodeficiencies [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%